Dynamic Resource Allocation Based Partial Crosstalk Cancellation in DSL Networks - Li, B; Tsiaflakis, P; Moonen, M; Maes, J; Guenach, M (2010 IEEE Global Telecommunications Conference GLOBECOM 2010, 2010)
The design of crosstalk mitigation techniques for DSL broadband access systems has mainly focused on physical layer transmit rate maximization. However, for certain applications, upper-layer performance metrics like network throughput, stability and delay performance may be more relevant. In this paper, we present a number of dynamic resource allocation based algorithms for partial crosstalk cancellation (PCC) that focus on these upper-layer metrics. A first algorithm focuses on preserving transmission queueing stability while maximizing the transmit rate. This is then extended towards budget adaptive algorithms, which dynamically adapt the PCC so as to improve the resource efficiency and to obtain a desirable trade-off between delay performance and resource consumption. Simulation results demonstrate the improved stability of the proposed algorithms and the obtained trade-off between delay performance and resource consumption.